The Concept of State and Government in Ibn Khaldun’s Thought - Neneng Sulastri (UIN Sunan Gunung Djati Bandung, 2019)
As a pioneer of the science of Sociology, in addition to reviewing the civilization of humanity from time to time, Ibn Khaldun often discussed the state and leadership. By laying down the principles of procedures for maintaining the existence of the state, he stressed that the dynamics and ups and downs of the state is a necessity. He then formulated this theory as Cycle Theory; that is a situation where a country experiences rapid progress at one time and will experience a setback and even collapse at another time. Departing from this, Ibn Khaldun often explained the importance of supporting elements of government. One of the most important elements in the state order according to Ibn Khaldun in his Muqaddimah is the figure of a leader. The ruler has an important role in maintaining the stability and sustainability of the country. One of the interesting things from other elements of forming a country is the concept of Asabiya. This concept plays an important role in determining the position of a ruler, determining state policy, even recruiting and eliminating elements whose benefits can be considered in the continuity of the state.